Typologia grup interesu artykułujących postulaty Kościoła katolickiego w Polsce - Kowalczyk, Krzysztof (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2017)
Celem artykułu jest dokonanie klasyfikacji grup interesu artykułujących postulaty Kościoła katolickiego w Polsce. W związku z tym zdefiniowano Kościół w ujęciu politologicznym, określono formy oddziaływania Kościoła na system polityczny, określono pojęcie grup interesu w odniesieniu do analizowanej problematyki, następnie w oparciu o określone kryteria dokonano ich typizacji. Zaproponowana typologia może stanowić punkt wyjścia do dalszych badań w tym zakresie.

The aim of the article is to classify interest groups divide the postulates of the Catholic Church in Poland. Accordingly, the Church was defined in terms of political science, the forms of the Church’s influence on the political system were defined, the concept of interest groups was defined in relation to the analyzed subject, and then based on specific criteria they were typified. The proposed typology may be the starting point for further research in this field.
Typology of interest groups divide the postulates of the Catholic Church in Poland
Keywords: Kościół katolicki w Polsce; Catholic Church in Poland; system polityczny; political system; grupy interesu; interest groups